2021
DOI: 10.3389/fmed.2021.695977
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Indwelling Pleural Catheter Based Management of Refractory Hepatic Hydrothorax as a Bridge to Liver Transplantation

Abstract: Introduction: Liver transplantation is the treatment of choice for decompensated liver disease, and by extension for hepatic hydrothorax. Persistent pleural effusions make it challenging for patients to maintain physiological fitness for transplantation. Indwelling pleural catheters (IPCs) provide controlled pleural fluid removal, including peri-operatively. The immune dysfunction of cirrhosis heightens susceptibility to bacterial infection and concerns exist regarding the sepsis potential from a tunnelled dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Patients who are unable to undergo a liver transplant, or are waiting for an organ to become available, may experience a transjugular intrahepatic portosystemic shunt (TIPS) or video-assisted thoracoscopy (VATS) to correct a diaphragmatic defect (16). Selvan et al (2021) reported indwelling pleural catheter-based management for hepatic hydrothorax as a bridge to liver transplantation (17).…”
Section: Cirrhosis Can Be Caused By Various Diseases Including Alcoho...mentioning
confidence: 99%
“…Patients who are unable to undergo a liver transplant, or are waiting for an organ to become available, may experience a transjugular intrahepatic portosystemic shunt (TIPS) or video-assisted thoracoscopy (VATS) to correct a diaphragmatic defect (16). Selvan et al (2021) reported indwelling pleural catheter-based management for hepatic hydrothorax as a bridge to liver transplantation (17).…”
Section: Cirrhosis Can Be Caused By Various Diseases Including Alcoho...mentioning
confidence: 99%